Három koncepció és ami utána következik... Közigazgatási reformtörekvések és kudarcaik sorozata Magyarországon 1945–1948 - Gyarmati, György (Tér és Társadalom, 1989)
Post-war years represented a period of radical transformations in Hungarian economic, social and political life. From the very beginning two–or, in a latent form, three–streams were converging in the process of transformation. One was derived from the necessity of the actual situation: consolidated living conditions had to be restored as soon as possible following war destructions. This program of reconstruction was integrated into various modernization concepts. The modernization programs can be divided into two contrasting groups. One direction intended to continue or revitalize a liberal modernization program–basically aimed at Hungary’s coming abreast of Europe in industrial and infrastructural development–complemented with social security guarantee, which was quashed by World War I following a few decades of prosperity around the turn of the century. The other direction, represented by the communists, involved the adoption of a Bolshevik model which they got acquainted with during their emigration in Stalin’s Soviet Union between the two world wars. The diverging perspectives outlined by the above concepts were, however, closely linked to the actual practical interests of the governmental coalition parties, i.e. to their fight for power against each other. The present paper follows the relationship between the need for modernization and the fight for power in a field where there was an agreement on the essentials, i.e. the need for radical transformation, among various parties. This was the field of organizational renewal in administration considered as a question of primary importance in particular party programs as well as by the sequent coalition governments of the time. The reform plans of three out of the four parties in governmental coalition–the National Peasant Party, the Social Democratic Party and the Small-holders’ Party–are published in full as an appendix to the paper. No such a comprehensive concept of the Communist Party can be reported on, simply because, in this field, the ’renewal’ efforts of the communists were concentrated on getting hold of key positions in the actual administration, i.e. on the personal metamorphosis instead of the organizational one. The analysis of the process highlights the means used by the Communist Party to block the elaboration of an organizational reform as long as it proved to be unable to enforce entirely its own ideas. This period lasted until the automn of 1947, the formation of the Cominform, the Information Bureau of Communist and Labour Parties. From the second half of 1947 the fight for power no longer meant to win the bent positions possible within a multi-party system of parliamentary structure but to confirm its own exclusive power by eradicating the pluralist establishment. The Communist Party’s take-over in 1948 defmitely dropped the matter of administration reform concepts based on strong local autonomies, and–within the frameworks of adopting the Bolshevik model–started the building up of a council system of the Soviet type.